TINGKAT PENDAPATAN ORANG TUA MENJADI FAKTOR UTAMA PERNIKAHAN DINI PADA REMAJA PUTRI - Andri Nur Sholihah; Nurma Yunita (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
The Early marriage is a topic that is seldom discussed anymore, yet despite the passage of time, this practice has not fully vanished. The goal of this research is to learn more about the factors that impact the rate of early marriage among young women. A descriptive correlation method with a cross sectional approach is used in the study design. At the Office of Religious Affairs (KUA) Gamping District, Sleman Regency, there are 34 young ladies under the age of 20 who are married. There were 34 persons in this study's sample. Total sampling is the sampling method used. A questionnaire is used as a research tool. Chi-Square is a statistical test. Parental income (0.043), respondent's education level (0.031), and respondent's attitude all have p-values less than 0.05 and impact early marriage.